PENINGKATAN PROFESIONALISME PEMBELAJARAN GURU DAN SISWA DENGAN MEDIA SPARKOL VIDIO SCRIBE - Risdheani, Ica; Anzaningtyas, Mita (Journal of Business Education and Social, 2022)
Sparkol is an application used to make videos with handwritten animations. In this application there are many cool and unique animations. So that it will make students more like and entertained in teaching and learning activities. But not only that, this software can also be used as a means of promotion, presentations, online business and other activities. With this software, it is easier for teachers to deliver material. in his research concluded, Video Scribe-based Compact Disc Interactive (CDi) learning media is valid to be used as a medium for supporting student independent learning in the Workshop Work Engineering (TKB) subject with an average rating of 88.55% which is in the very valid category , the practical value of the Video Scibe-based Compact Disc Interactive (CD-i) learning media was stated to be very good.